Family systems psychiatry in an acute in‐patient setting: the implementation and sustainability 5 years after its introduction. Issue 2 (10th February 2012) - Haun, Markus W.; Kordy, Henrike; Ochs, Matthias; Zwack, Julika; Schweitzer, Jochen
<x xml:space="preserve">Abstract</x> From 2003 to 2008 a multicentre research project, systems therapy methods in acute psychiatry (SYMPA), attempted to establish structured in‐patient treatment based on systemic interventions in German non‐university psychiatric hospitals. Utilising multi‐professional family systems training for team members in six in‐patient wards, its main goal was to improve the involvement of familial and non‐familial important others. This follow‐up study explores the sustainability of family systems psychiatry by evaluating the frequency of the utilisation of four core systemic interventions; elements of a systemic organizational culture in psychiatry; and institutional barriers to this new approach. The degree of implementation was high to moderate, depending on the intervention. More intense communication developed among staff of different professions and the status of nursing staff improved. Organizational barriers to implementation included the ambiguous role of junior doctors in teams, continuously understaffed wards and frequent over‐occupancy.